The effect of oral administration of Eurycoma longifolia extract on body weight and blood pressure in Sprague dawley rats fed high-fat diet - Al-Joufi, Fakhria; Saxena, Anil Kumar; Al-Ani, Imad Matloub Dally; A.Talib, Norlelawati; Mokhtar, Rafidah Hanim; Ku Zaifah, Norsidah (2015)
Hypertension is one of the most important risk factors for cardiovascular events. It has become a sigaificant socioeconomic burden in many countries" Eurycoma longifolia (EL), Simaroubaceae, is a herb that has been used since ancient times to combat many health problems. Its effects are attributed to its bioactive constituents. This study focused on the effects of EL on blood presswe (BP) and body weight (BSD in rats fed high-fat (I{F). Healthy male SD rats wete randomly divided into 4 groups (n:6) and were orally fed the following diets: 1) Normal diet alone (ND); 2) Normal diet plus EL [15 mdke] QID+EL); High-Fat diet (53%) alone (]IFD); High-Fat diet (53%) plus EL [15 mglkg] (I{FD+EL). EL extract was oraliy administered for 12 weeks. Systolic blood pressure (SBP) and diastolic blood pressure (DBP) were measured at week 0, 6 and 72 by using CODA@ tail-cuff BP system while the BW was measured weekly. Statistical significance was determined by repeated measure (ANOVA) and one-way (ANOVA). P values < 0.05 were considered significant. Administration of EL led to less increment in BW OrD (34%) vs. NDEL (21%) and IIFD (37%) vs. IIFDEL (25%)) but did not achieve significant level. No changes in SBP and DBP were demonstrated zlmong the experimental groups at week 0. In addition, ND and NDEL groups did not show any significant difference in SBP and DBP (p > 0.05) over the period of the study. Although, the SBP and DBP were significantly increased in IIFD and IIFDEL compared to ND $<0.05), the SBP and DPB were significantly reduced in IIFDEL as compared with IIFD 1p: 0.001) over the period of study. This study showed that the potential BW reduction effect of EL and its anti-hypertensive property by providing a significant reduction in SBP and DBP"